machine functionality Lawn mowing (Journal of the College of Basic Education, 2022)
The research problem lies in the fact that some of the design systems used for some grass cutting machines are not suitable for human performance, in addition to that the mechanical parts do not perform their function properly due to the variable dimensions of the machine.